The genetic program of oocytes can be modified in vivo in the zebrafish ovary. (28th July 2018) - Wu, Xiaotong; Shen, Weimin; Zhang, Bingjie; Meng, Anming
Abstract: Oocytes, the irreplaceable gametes for generating a new organism, are matured in the ovary of living female animals. It is unknown whether any genetic manipulations can be applied to immature oocytes inside the living ovaries. As a proof-of-concept, we here demonstrate genetic amendments of zebrafish immature oocytes within the ovary. Oocyte microinjection in situ (OMIS) stimulates tissue repair responses, but some of the microinjected immature oocytes are matured, ovulated and fertilizable. By OMIS-mediated Cas9 approach, ntla and gata5 loci of oocytes arrested at prophase I of meiosis are successfully edited before fertilization. Through OMIS, high efficiency of biallelic mutations in single or multiple loci using Cas9/gRNAs allows immediate manifestation of mutant phenotypes in F0 embryos and multiple transgenes can co-express the reporters in F0 embryos with patterns similar to germline transgenic embryos. Furthermore, maternal knockdown of dnmt1 by antisense morpholino via OMIS results in a dramatic decrease of global DNA methylation level at the dome stage and causes embryonic lethality prior to segmentation period. Therefore, OMIS opens a door to efficiently modify the genome and provides a possibility to repair genetically abnormal oocytes in situ .